IMPROVING STUDENTS’ ACHIEVEMENT IN WRITING DESCRIPTIVE PARAGRAPH THROUGH THE FIVE-SENSE TECHNIQUE - Claudya Sinaga; Sri Juriaty Ownie (Universitas Negeri Medan, 2013)
This study is aimed to find out whether the five-sense technique can improve the students’ achievement in writing descriptive paragraph. This study was conducted by using Classroom Action Research. The subject of this study is the second grade VIII-B students of SMP Trisakti 2 Medan. The number of the subject was 30 students. This thesis applied in two cycle and six meetings. The qualitative data were taken from diary notes, observation sheet and questionnaire sheet. The quantitative data were taken from the mean of the students’ score in writing test. Based on the data, the students’ score got improvement in every cycle. In Test I, the mean of the students’ scores was 61.43 while in Test II, the mean of the stydents’ scores was 70.46 and in Test III, the mean of students’ scores was 77.93. Based on the result of quantitative data, it was found that there was improvement on students’ achievement in writing descriptive paragraph.